Development of a Point Pyroshock Source Simulator. (6th February 2017) - Jeong, Ju-won; Lim, Jae hyuk; Kim, Kyung-won; Lee, Jung-ju
Abstract : We developed a point pyroshock source simulator (PPSS) for the study on the source isolation approach (SIA) in this study. In spite of the potentiality of the SIA for avionics protection against pyroshock, it has rarely been investigated due to lack of pyroshock source simulators. To overcome such a situation, we proposed the PPSS using a mechanically excited tuned resonator simulating a release device itself. The PPSS was designed using explicit finite element analysis and Seigel's gas gun model. To verify the proposed PPSS, the prototype was fabricated and tested. From the results, we have shown that the prototype of the PPSS simulates a near-field pyroshock and is able to evaluate the SIA.